Influence of Audit Committee Independence on the Quality of Audit Reports of Sacco’s in Homabay County, Kenya - Limonya, Joel Okinyu (International Journal of Business, Economics, and Social Development, 2024)
Every operating organization keeps tabs on its development by producing accurate financial statements at the conclusion of each fiscal year, which are subsequently distributed to various individual users who are concerned with the organization's development. The accuracy of the financial accounts is then verified by an audit procedure, which is sealed by a transparent audit report provided to the specific business by the audit committee. The main objective of this study was to examine the influence of audit committee independence on the quality of audit reports of Sacco’s in Homabay County, Kenya. This was supported by the fact that there are numerous Sacco’s in Homabay County, many of which had apparently experienced audit problems in the past. Stakeholders’ theory served as the study's compass. This study adopted a descriptive causal research design, the target population was 104 audit committee members of deposit taking Sacco’s in Homabay County as at December 2021. Out of the target population determined using the Krejcie and Morgan formula, 82 members of the audit committee provided responses for the study. Primary data was collected using research questionnaire which involved drop and pick method. Descriptive statistics including a frequency table, mean, and standard deviation were used for data analysis while inferential statistics included Pearson’s correlation analysis. The study found that audit committee independence in Homabay County, Kenya, had a positive and significant impact on the caliber of audit reports on Sacco’s (r=0.530, p<0.05). The study recommends that Sacco’s audit committee members should be as independent as possible in executing their mandate so as to ensure audit reports provided are of quality.